WILLINGNESS TO WORK ABROAD AMONG NURSING STUDENTS AT TRA VINH UNIVERSITY IN 2024 (Vietnam Journal of Community Medicine, 2026)
Abstract: Growing international demand for nurses has expanded overseas employment opportunities for nursing graduates, including those in Vietnam. However, evidence on Vietnamese nursing students’ willingness to work abroad remains limited.Objectives: To assess the proportion of nursing students’ willing to work abroad, their preferred destinations, perceived barriers, and associated factors.Methods: A descriptive cross-sectional study was conducted from May to July 2024 among undergraduate nursing students (years 1–4) at Tra Vinh University, Vietnam (n = 430). Data were collected using a structured questionnaire covering demographic characteristics, willingness to work abroad, preferred destinations, and perceived barriers, and analyzed with descriptive statistics and chi-square tests.Results: Overall, 51.6% of students reported willingness to work abroad. Japan (50.9%) and Germany (32.0%) were the most preferred destinations. The main perceived barriers were language limitations (75.2%) and insufficient professional preparedness (54.5%). Anticipated challenges during overseas employment included job pressure (73.4%) and cultural differences (57.2%). Living arrangement was the only factor significantly associated with willingness to work abroad (p = 0.045).Conclusions: More than half of nursing students expressed intention to pursue overseas employment, particularly in Japan and Germany. Addressing language proficiency, clinical readiness, and pre-departure preparation is essential to support students’ international career aspirations while ensuring sustainable workforce development.
Keywords: Nursing students,Willingness to work abroad, Overseas employment